Member stability of stainless steel welded I-section beam-columns. (April 2019) - Yang, Lu; Zhao, Menghan; Gardner, Leroy; Ning, Keyang; Wang, Jie
Abstract: A comprehensive experimental and numerical study is presented into the behaviour of stainless steel welded I-section beams-columns. Twenty test specimens were fabricated from grade 304 (EN 1.4301) austenitic and grade 2205 (EN 1.4406) duplex stainless steel plates – ten were tested under major axis bending plus compression and ten under minor axis bending plus compression. Material tensile coupon tests and geometric imperfection measurements were also conducted. Numerical models were developed, calibrated against the test results and subsequently employed in parametric studies considering a wider range of specimen geometries. Based on the obtained test and numerical results, the accuracy and reliability of existing design rules given in EN 1993-1-4 and AISC DG 27, as well as recent proposals, were assessed. Highlights: A comprehensive experimental programme including 20 beam-column tests was carried out. Finite element models were validated against test results, and used to perform parametric studies. The accuracy of existing design rules given in EN 1993-1-4 and AISC DG 27, as well as recent proposals, were assessed.